Orientation Control of Graphene Flakes by Magnetic Field: Broad Device Applications of Macroscopically Aligned Graphene. Issue 1 (10th November 2016) - Lin, Feng; Zhu, Zhuan; Zhou, Xufeng; Qiu, Wenlan; Niu, Chao; Hu, Jonathan; Dahal, Keshab; Wang, Yanan; Zhao, Zhenhuan; Ren, Zhifeng; Litvinov, Dimitri; Liu, Zhaoping; et al.
Abstract : Owing to a large diamagnetism, graphene flakes can respond and be aligned to magnetic field like a ferromagnetic material. Aligned graphene flakes exhibit emergent properties approaching single‐layer graphene. Anisotropic optical properties also give rise to a magnetic writing board using graphene suspension and a bar magnet as a pen. This simple alignment technique opens up enormous applications of graphene.